Biochemical and Microbiological Changes of Caryota urens (Kithul Palm) Phloem Sap - Jayathilake, A.N.; Wijeyaratne, S.C. (My University, 1999)
Biochemical and microbiological changes that occur during fermentation of Caryota urens phloem sap were studied with a view to conducting basic research for later upgrading the local fermentation industry and to developing new biotechnological processes by recognizing yeasts suitable to local conditions. Sap, which was taken after keeping a sterilized pot for 10 hours was free of alcohol, showing that fermentation has not taken place yet. Paper chromatographic studies done with this unfermented sap revealed that the main type of sugar was sucrose while glucose and fructose were in trace amounts. The content of reducing sugar of phloem sap at the time of collection was very.low (0.14%). However this started to increase after 24 hours and reached a maximum value of (4.1 %w/v) after 24 hours. The alcohol concentration, measured by ebulliometer, increased only after appreciable quantities of reducing sugars was formed. Maximum alcohol concentration of7% v/v was obtained on the fifth day. The unfermented sap had a pH around 7. The pH value decreased substantially and reached a constant value around 4 after the fourth day of fermentation. Decrease in pH coincided well with increase of acidity. Microbial analysis of fermenting sap revealed that the type of orgnisms present in the sap changed with time. At the beginning of fermentation the sap contained mainly bacteria with a colony count in the order of 107 cellsl ml. They were found to be mainly Lactobacilli and Leuconostoc. The yeast cells were very few in number initially but increased after 24 hours and reached a maximum of8x 107 cell/rnl after the third day. During the latter stages of fermentation, there was a drop in the viable yeast cell count, while the bacterial count increased again to 1()6cells/ml. A total of eleven yeast strains were isolated from fermenting phloem sap. Saccharomyces cerevisiae was found to be the most predominant yeast species. In the early stages Candida tropicalis and Pichia membranifaciens were found to be abundant.
Keywords: Caryota urens; Palm phloem sap; Kithul palm sap